CFD modelling of ventilation optimization for improving mine safety in longwall working faces - Cheng, Jianwei; Li, S.; Zhang, F.; Zhao, C.; Yang, S.; Ghosh, A. (2016)
© 2016 Elsevier Ltd. Mining coal seams with high coal gas content and coal spontaneous combustion (SponCom) risk is often a challenge for mining engineers. Control measures for maintaining the gas concentration under the regulation permissible limit (Generally 1%) as well as reducing coal fire risks must be taken simultaneously in order to create safety production conditions. However, in reality, such measures either for gas or for fire problems are sometimes conflictive. For an example, the basic strategy of gas control in underground is to increase the ventilation airflow for sweeping the longwall working face and diluting the gas concentration, but it also results in leakage of an amount of air into the mine gob area sufficient to support the coal SponCom development process. Conversely, sealing or isolating mine gob areas can easily cause the gas accumulation which may increase the gas explosion risk. To conquer this dilemma situation, it is necessary to deeply understand the coupling relationship between the mine gases and coal SponCom controls. In this paper, based on a real case in an underground coal mine, a ventilation parameters optimization research is conducted by using the Computational Fluid Dynamics (CFD) simulation approach for solving the stated contradiction problems to derive the optimum solutions for both managing gas hazards and fire risks in the underground. In this study, the boundary conditions are fully considered in accordance with the reality. A list of important ventilation parameters including the air quantity supplied to the mine working face, the negative ventilation pressure in the roof roadway for gas drainage and reasonable distributed airflow quantity in tailgate roadways, are investigated. The research findings balance the requirements both for gas control and fire-prevention. The proposed method could be applied to guide the mine design practices in improving safety.